2019
DOI: 10.1002/sdtp.13013
|View full text |Cite
|
Sign up to set email alerts
|

50‐2: Towards Modern Burn‐in Assessment Method for HDR Displays

Abstract: A novel burn-in assessment method is strongly required for modern high dynamic range (HDR) displays. Specifically, one of the necessary requirements for the new method is to stimulate a maximum capability of HDR displays such as a wide color gamut for all colors and a wide range of luminance. In this paper, based on the requirements, a new burn-in assessment method is proposed by employing steepest gradient weighted quantification metric. Experimental results and analysis are conducted for validating the propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The fitting factors β=0.934 and τ=16271.6 for white picture with 255 gray scale, and the longer attenuation trend of this batch of samples can be fitted according to SED model. It can be seen from Figure (1) that the prediction curve of the SED model at room temperature can be well fitted with the actual measured curve. Therefore, in the pre-processing stage of De-Burn in(DBI) algorithm, most of the SED model is used to predict the attenuation trend of the same batch of samples, and the compensation model is established according to the predicted attenuation trend.…”
Section: Oled Luminance Attenuation Modelmentioning
confidence: 63%
See 1 more Smart Citation
“…The fitting factors β=0.934 and τ=16271.6 for white picture with 255 gray scale, and the longer attenuation trend of this batch of samples can be fitted according to SED model. It can be seen from Figure (1) that the prediction curve of the SED model at room temperature can be well fitted with the actual measured curve. Therefore, in the pre-processing stage of De-Burn in(DBI) algorithm, most of the SED model is used to predict the attenuation trend of the same batch of samples, and the compensation model is established according to the predicted attenuation trend.…”
Section: Oled Luminance Attenuation Modelmentioning
confidence: 63%
“…OLED display does not need to carry backlight plate due to its self-luminous characteristics. Therefore, it has the advantages of thin, low power consumption, high contrast, high refresh rate and so on, and is widely used in mobile devices, wearable display, vehicle display, flexible display, and other fields [1] [2] . Active Matrix Organic Light-Emitting Diode (AMOLED) can be emitting by adding the technology of Thin film transistor (TFT) backplane.…”
Section: Introductionmentioning
confidence: 99%
“…Notice that the checkerboard test pattern was stressed at the given conditions and then move to an initial test pattern to examine residual image from the white and black area. It has been reported that IS is affected by luminance gradients [15]. Using the equation ( 1), the IS index is calculated.…”
Section: Image Sticking and Characterizationmentioning
confidence: 99%
“…The nonuniform degradation, recognized as the burn‐in phenomenon, occurs depending on the amount of accumulated current density delivered to each pixel unevenly in the display panel. This quality degradation can be more serious when an OLED display is used in the high dynamic range (HDR) 2 and under display camera (UDC) applications because these require more current consumption to drive the pixels in high luminance, and therefore, it is more likely to be burned in less time. It is also known that the burn‐in artifact becomes visible even at the luminance deviation of 3% between adjacent pixels 3 …”
Section: Introductionmentioning
confidence: 99%